2017
DOI: 10.1515/otmcj-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of project management on quality during the early phases of construction projects

Abstract: Abstract:Although the quality of a process affects the quality of the end product, there is currently an insignificant amount of knowledge about the quality of project management (PM) processes that directly affect the quality of the delivered product (constructed building). This study presents a proposal for modeling the impact of the quality of the PM process on the quality of the constructed building. The quality of the PM process is represented by the main quality factors and product quality indicators. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The previous study performed by authors analysed F1-F11 (Table 3) process factors, factor F8 "coordination between project participants" (investor, contractor, and project manager) ranked first [22]. The survey participants believe it is the most important, but it is not the most mentioned factor in analysed papers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The previous study performed by authors analysed F1-F11 (Table 3) process factors, factor F8 "coordination between project participants" (investor, contractor, and project manager) ranked first [22]. The survey participants believe it is the most important, but it is not the most mentioned factor in analysed papers.…”
Section: Discussionmentioning
confidence: 97%
“…The information was either presented by authors or found based on affiliation. We found 32 countries, with the largest number of papers in the USA (22), China ( 16), UK (13), and Malaysia (9). Papers grouped by continents and years of publication present how the idea of quality management in construction project management spread throughout the world (Figure 2).…”
Section: Descriptive Analysismentioning
confidence: 99%